EHealth literacy and web‐based patient portal usage among kidney and liver transplant recipients. Issue 2 (16th December 2020) - Maroney, Kieran; Curtis, Laura M.; Opsasnick, Lauren; Smith, Kayla D.; Eifler, Morgan R.; Moore, Amy; Wedd, Joel; Wolf, Michael S.; Patzer, Rachel E.
Abstract: Patient portals promote self‐management, but require skills with electronic health information which can be measured by a patient's eHealth literacy. We aimed to describe eHealth literacy among a population of kidney transplant (KT) and liver transplant (LT) recipients and to investigate the relationship between eHealth literacy and Web‐based patient portal utilization. We conducted phone surveys (August 2016‐March 2017) among 178 KT and 110 LT recipients at two large transplant centers, including the eHealth Literacy Scale (eHEALS) and items assessing routine portal usage. Portal users were defined as routine if usage was every day, weekly, or monthly. The mean eHEALS score was 30.9 (SD: 5.4), and 45.4% routinely used the patient portal more than a few times per month. Routine users had higher eHealth literacy than non‐routine users and non‐users (31.97 vs. 29.97 vs. 28.20, p < .001). Routine users had higher eHealth literacy scores compared with non‐users after adjusting for transplant organ type, age, educational level, employment status, mobile Internet access, and transplant center (OR: 1.10, 95% CI: 1.03‐1.17). KT and LT recipients who routinely use patient portals have high eHealth literacy compared with other diseased populations, which should be leveraged by encouraging routine usage to improve post‐transplant health and medication adherence.